Paul Ricoeur y la noción de conatus de Spinoza - Olaechea Catter, Jorge (2024)
Even though Paul Ricoeur did not write an entire work about Spinoza, many interpreters have pointed out the relevance of the thought of the Dutch philosopher—and specially of his Ethics—to Ricoeur’s oeuvre. This paper seeks to show the significance of Spinoza’s notion of conatus in the hermeneutical and ontological approach of the French philosopher. Specifically, it analyses an important conceptual node in the last Study of Oneself as Another. The analysis mainly considers those passages of Spinoza’s works that are quoted. It tries to expand the understanding of them considering the context in which they appear, in order to see if this allows to confirm the abovementioned relevance of Spinoza in Ricoeur’s philosophy.